Single nucleotide polymorphisms associated with P2X7R function regulate the onset of gouty arthritis. - Jin-Hui Tao; Miao Cheng; Jiang-Ping Tang; Xiao-Juan Dai; Yong Zhang; Xiang-Pei Li; Qin Liu; Ya-Ling Wang (PLoS ONE)
Background Gout is an inflammatory disease that is caused by the increased production of Interleukin-1β (IL-1β) stimulated by monosodium urate (MSU) crystals. However, some hyperuricemia patients, even gouty patients with tophi in the joints, never experience gout attack, which indicates that pathogenic pathways other than MSU participate in the secretion of IL-1β in the pathogenesis of acute gouty arthritis. The ATP-P2X7R-IL-1β axis may be one of these pathways. Objective This study examines the role of Adenosine triphosphate (ATP) in the pathogenesis of gout and the association of ATP receptor (P2X7R) function with single nucleotide polymorphisms and gout arthritis. Methods Non-synonymous single nucleotide polymorphisms (SNP) loci of P2X7R in Chinese people were screened to compare the frequencies of different alleles and genotype distribution of selective SNPs in 117 gouty patients and 95 hyperuricemia patients. Peripheral white blood cells were purified from the peripheral blood of 43 randomly selected gout patients and 36 hyperuricemia patients from the total group. Cells were cultured with MSU or MSU + ATP, and supernatants were collected for the detection of IL-1β concentrations using enzyme-linked immunosorbent assay (ELISA). Results 1. Eight SNP loci, including rs1653624, rs10160951, rs1718119, rs7958316, rs16950860, rs208294, rs17525809 and rs2230912, were screened and detected, and rs1653624, rs7958316 and rs17525809 were associated with gout arthritis. 2. IL-1β concentrations in supernatants after MSU + ATP stimulation were significantly higher in gouty patients than in the hyperuricemia group [(131.08 ± 176.11) pg/ml vs. (50.84 ± 86.10) pg/ml]; Patients (including gout and hyperuricemia) carrying the susceptibility genotype AA or AT of rs1653624 exhibited significantly higher concentrations of IL-1β than patients carrying the non-susceptibility genotype TT [(104.20 ± 164.25) pg/ml vs. (21.90 ± 12.14) pg/ml]; However, no differences were found with MSU stimulation alone. Conclusions ATP promotes the pathogenesis of gouty arthritis via increasing the secretion of IL-1 β, and its receptor (P2X7R) function associated single nucleotide polymorphisms may be related to gouty arthritis, which indicates that ATP-P2X7R signaling pathway plays a significant regulatory role in the pathogenesis of gout.